REACTION OF ADENINE WITH AN ALPHA-CHLOROOXETANE - AN APPROACH TO THE SYNTHESIS OF OXETANE NUCLEOSIDES - Fleet, G; Son, J; Vogt, K; Peach, J; Hamor, T (1988)
The reaction of adenine with 3,5-anhydro-5R-chloro-1,2-O- isopropylidenexylofuranose, a stable α-chlorooxetane, gives a mixture of the two epimers of 5-[9-adenyl]-3,5-anhydro- 1,2-O-isopropylidenexylofuranose; the structure of 5R-[9- adenyl)-3,5-anhydro-1,2-O-isopropylidenexylofuranose was established by X-ray crystallography. © 1988.